(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
In the Constitution there are no legislative provisions expressly dedicated to the rights of immigrants, but its reading shows that adequate health care should be guaranteed by the legislator to all foreigners living in Italy. For this reason, the single text on immigration also protect-ed the health of irregular foreigners and the decree updating the levels of assistance made it clear that access to care for these subjects is similar to that guaranteed to immigrants with a res-idence permit. However, in our legislation the therapies to be ensured to irregular foreigners have not been precisely identified. Therefore, a legislative reform is desirable which, guaranteeing all immigrants extensive health care, is more respectful of the constitutional order.